2019
DOI: 10.1016/j.nucengdes.2019.110227
|View full text |Cite
|
Sign up to set email alerts
|

Vibrations in a 7-rod bundle subject to axial flow: Simulations and experiments

Abstract: Being able to quantify mechanical vibrations is of key importance for the safety of nuclear power plants, as they are able to induce damage. In this work, numerical simulations are used to compute water flow and vibration in a densely packed bundle of 7 rods, mimicking an experimental setup. This flow configuration is chosen to resemble the coolant flow through a nuclear reactor core. Because of the wall proximity, a considerable velocity difference between the narrow gaps and the subchannels exists, with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Next to increasing confidence in simulation results of a realistic reactor envi-ronment, also a second reason to resort to UQ methods can be given. Geometrical or operational uncertainties are present in experiments (Roelofs et al, 2019) and can convolute numerical validations, as was suggested by Dolfen et al (2019) and Bertocchi et al (2020). This is especially the case because FIV experiments are typically complicated to construct.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Next to increasing confidence in simulation results of a realistic reactor envi-ronment, also a second reason to resort to UQ methods can be given. Geometrical or operational uncertainties are present in experiments (Roelofs et al, 2019) and can convolute numerical validations, as was suggested by Dolfen et al (2019) and Bertocchi et al (2020). This is especially the case because FIV experiments are typically complicated to construct.…”
Section: Introductionmentioning
confidence: 97%
“…The simulation data and pre-and post-processing scripts are available for download on the Zenodo platform (Dolfen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…De Moerloose et al 8 ) or simulating the dynamic behavior of the cylinder itself using fluid-structure interaction (FSI) simulations (e.g. Liu et al 9 , Liu et al 10 , De Ridder et al 11 , Dolfen et al 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the ever-increasing computational power, more and more numerical research is being performed. Some examples have already been mentioned (Liu et al 9 , Liu et al 10 , De Ridder et al 11 , Dolfen et al 12 ) for a clamped-clamped structure. The clamped-free configuration typically has a larger range of motion, which poses additional difficulties to the numerical modelling, which could explain why very limited numerical research has as of yet been performed on the topic.…”
Section: Introductionmentioning
confidence: 99%